Adherence of patients to oral oncolytic and neurologic specialty medications provided by a specialty pharmacy. (3rd September 2019) - Burruss, Royce; Bhusal, Binita; Oleru, Kiona; Arikian, Veronica; Jaster, Ryan; Stranz, Marc; Lindhorst, Justin
Abstract: Background: Specialty medications (SP-D) are high cost prescription medications designed for the treatment of complex chronic conditions, i.e. cancer and neurological diseases. Such medications require special handling and shipping, administration, and patient education. To achieve the desired treatment outcomes, including minimizing adverse events, medication adherence is key. There are barriers to poor medication adherence, some of which include high cost, poor understanding of disease and associated therapy, psychological status, forgetfulness, complex dosing regimens, and side-effects. The consequences of non-adherence include increased healthcare resource consumption and poor disease treatment outcomes, e.g. increased relapse, decreased survival time, and/or lack of patient satisfaction. Specialty pharmacy provided medication therapy management (SPMTM) can be important to achieving acceptable medication adherence and, therefore, better treatment outcomes. The specialty pharmacy is a community pharmacy focused on dispensing and providing clinical services pertaining to SP-D. It has pharmacy permits in 50 states as well as in Washington DC, Puerto Rico, and the US Virgin Islands. It is accredited by URAC and ACHC as a specialty pharmacy. Some of the key services provided by specialty pharmacy are: oncology, neurology, autoimmune disease, analgesia (non-controlled drug), investigational drugs, and other SP-D to treat rare/ultra-rare conditions. Aims: The primary objective of the study was to measure the adherence rate to the oncology and neurology SP-D dispensed by the specialty pharmacy. The secondary objective of this study is to compare the quality-of-life (QoL) of patients who voluntarily participated in the SPMTM program at the program's start of care (SOC) assessment (before the SP-D had been started) and at the follow-up (F-U) assessment (after SP-D had been started). Methods: A retrospective, observational study of patient reported outcomes (PRO) was conducted at a specialty pharmacy among patients diagnosed with various forms of cancers and neurological issues who had prescriptions filled for SP-D from January 1, 2018 to December 31, 2018. Patient education by the pharmacist was offered as part of the SPMTM program throughout patient participation in the program. Each patient was offered medication therapy assessment at SOC and 7 days prior to each refill dispense, using a proprietary clinical assessment instrument designed to capture patient reported data via telephonic interview with patients or their caregivers. Embedded in the assessment instruments were two QoL PRO metrics: (1) Number of days work/school missed; and (2) How have you been feeling? (1–10 scale, where 1 was feeling terrible and 10 was feeling wonderful). The means of the SOC (BEFORE SP drug state) and the F-U (AFTER SP drug state) data were captured monthly and annualized. The annualized means were compared, using the Mann-Whitney U-value (M-WU) two-tailed statistic to test for a statistically significantdifference between the annualized means of the respective QoL measures at the p  < 0.05 level of significance. In addition, the overall mean of the Proportion of Days Covered (PDC) was calculated, using the URAC PDC formula. Results: The total number of unique patients was 39, 567, and the average number of dispenses per unique patient was two. The number of unique patients who voluntarily participated in the SPMTM program and received clinical assessments was 33, 243 (84%); 6, 331 (16%) patients declined to participate in the SPMTM program. The number of patients who completed only the SOC assessment was 19, 946 (60%); the number of patients who participated in only F-U assessment was 3, 324 (10%); and the number of patients who participated in both assessments was 4, 322 (13%). The overall mean annual Proportion of Days Covered (PDC) was 0.962 (96.2%). The medication adherence rate is 20.25% higher as compared to the industry standard adherence rate of ∼80%. The mean Days of work/school missed QoL metric at SOC was 0.16 days and it was 0.02 days after F-U assessment. The annualized mean difference in work/school days missed demonstrated an improvement between before and after receiving SP-D, and SPMTM was 0.14 days. The Mann-Whitney U-value (M-WU) was determined to be 4, which had a calculated p  = 0.0001, and the M-WU value at the p  < 0.05 level was 37. The How have you been feeling QoL metric annualized mean at SOC assessment was 7, and the annualized mean at refill assessment was 7.46. The total improvement in feeling is 0.46 higher on the 10-point scale. Therefore, patients reported improvement in how they felt after taking SP-D and participating in the SPMTM program. The M-WU value is 4, and calculated p  = 0.0001. The critical value of M-WU at p  < 0.05 is 37. Conclusions: From this 1-year study it was determined that: (1) the annualized PDC adherence rate of 0.96 was 20.25% higher than the industry standard of 0.8; (2) the Number of days work missed QoL was less after starting on a SP-D with SPMTM; and (3) the How patients feel QoL metric demonstrated that patients felt better after starting SP-D with SPMTM. The improved adherence rate was associated with taking the SP-D while participating in the SPMTM. The encouraging findings of this study suggest that additional larger studies should be conducted.